Новый вид панцирного клеща (Archoribatida, Phthiracaridea) из Украины - Сергиенко, Г.Д. (Вестник зоологии, 2000)
Описан новый вид Calyptophthiracarus concolor sp. n. из Крыма. Отличается от хорошо известных видов числом щетинок на нотогастре и их опушением, размещением щетинки с3. Типовые экземпляры хранятся в Институте зоологии им. И. И. Шмальгаузена НАН Украины (Киев). Calyptophthiracarus concolor sp. n. is discribed from the Crimea. It differs from other well-known species by the number of notogaster setae, their pubescence, the place of seta ñ3, the form of sensillus, long lamelar setae, presence of one seta on the genu leg IV. Type specimens deposited in the Shmalgausen Institute of Zoologii NAS of Ukraine (Kyiv).